2009
DOI: 10.3109/00048670903270399
|View full text |Cite
|
Sign up to set email alerts
|

Does School Bullying Affect Adult Health? Population Survey of Health-Related Quality of Life and Past Victimization

Abstract: Adults commonly reported experiencing bullying while at school and these reports were associated with lower health-related quality of life in adulthood. School bullying needs further investigation as a preventable cause of mental health problems across the lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 14 publications
3
71
1
2
Order By: Relevance
“…However, unlike a previous Australian study in adults 23 using the Short Form Health Survey in which earlier bullyingvictimization experiences significantly affected psychological HRQOL, this study did not find such a significant association. Other than differences in the study population and measures used, it is worth noting that our study controlled for depression, a mental disorder that commonly occurs after bullying-victimization experiences.…”
Section: Physical Health and Environment Domains: Cyber Bullying-victcontrasting
confidence: 55%
See 2 more Smart Citations
“…However, unlike a previous Australian study in adults 23 using the Short Form Health Survey in which earlier bullyingvictimization experiences significantly affected psychological HRQOL, this study did not find such a significant association. Other than differences in the study population and measures used, it is worth noting that our study controlled for depression, a mental disorder that commonly occurs after bullying-victimization experiences.…”
Section: Physical Health and Environment Domains: Cyber Bullying-victcontrasting
confidence: 55%
“…But it is NOT BULLYING when two students of about the same strength quarrel or fight." 8,23 In addition to this statement, definitions and examples of the 4 types of bullying (physical, verbal, relational, and cyber), as described previously, were also provided to the participants on the questionnaire. For each type of bullying, the time periods of occurrence included the following: never, precollege, in-college (ie, while enrolled as a college student), and in both periods (ie, both before and in college).…”
Section: Bullying Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the retrospective studies reviewed in this paper have suggested an association between being bullied at school and long-term psychic adjustment (Chapel et al, 2008;Dempsey and Storch, 2008;Allison, 2009;Orth, 2009). As previously discussed, adults with a history of being bullied are likely to develop depression, anxiety, personality disorder, and loneliness.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
“…Moreover, Allison et al (2009) show that adults who had been bullied as children reported poorer mental and physical health compared to those who had not been bullied.…”
Section: Introductionmentioning
confidence: 99%